Adoption of dental innovations: The case of a standardized dental diagnostic terminology - Ramoni, Rachel B. (J Am Dent Assoc, 2017)
BACKGROUND: Standardized dental diagnostic terminologies (SDDxTs) were introduced decades ago. Their use has been on the rise, accompanying the adoption of electronic health records (EHRs). One of the most broadly used terminologies is the Dental Diagnostic System (DDS). Our aim was to assess the adoption of SDDxTs by US dental schools by using the Rogers diffusion of innovations framework, focusing on the DDS. METHODS: The authors electronically surveyed clinic deans in all US dental schools (n = 61) to determine use of an EHR and SDDxT, perceived barriers to adoption of an SDDxT, and the effect of implementing an SDDxT on clinical productivity. RESULTS: The response rate was 57%. Of the 35 responses, 91% reported using an EHR to document patient care, with 84% using axiUm, and 69% reported using an SDDxT to document patient diagnoses; 41% used the DDS. Fifty-four percent of those who did not use an SDDxT had considered adopting the DDS, but 39% had not, citing barriers such as complexity and compatibility. CONCLUSIONS: Adoption of an SDDxT, particularly the DDS, is on the rise. Nevertheless, a large number of institutions are in the Rogers late majority and laggards categories with respect to adoption. Several factors may discourage adoption, including the inability to try out the terminology on a small scale, poor usability within the EHR, the fact that it would be a cultural shift in practice, and a perception of unclear benefits. However, the consolidation of the DDS and American Dental Association terminology efforts stands to encourage adoption.